Can Donors and Nonstate Actors Undermine Citizens' Legitimating Beliefs? - Sacks, Audrey (World Bank, Washington, DC, 2014)
Under what conditions is service provision by donors and non-state actors likely to undermine or strengthen citizens' legitimating beliefs? A new study assesses associations between donor and non-state actor service provision and the sense of obligation that these associations produce for citizens to comply with tax authorities, the police, and courts. This note presents the study's findings, which suggest that the provision of services by donors and non-state actors is strengthening, rather than undermining, the relationship between citizens and the state.